Monitoring the impacts of marine aggregate extraction : Knowledge Synthesis 2012 (GIS SIEGMA) - Robert Lafite (Presses universitaires de Rouen et du Havre, 2014)
This document is a comprehensive survey of the scientific knowledge acquired in late 2012 on the environmental impacts of marine aggregate extraction. The synthesis completes international knowledge (ICES WGEXT, COST Action 638 "MAGGNET") with local investigation in Normandy on two sites of the Eastern English Channel in the framework of the 2003-2011 SIEGMA programme.